Evolution de la mortalité des huîtres portugaises C. angulata dans le bassin de Marennes - Comps, Michel; Gras, Paul (Actes CIEM, CM 1973/K:15, 1973)
A year after the end of the Gill disease which heavily struck the Portuguese oysters Cassostrea angulata Lmk. (Marteil, 1968), a new disease whose causes are still unexplained caused a massive mortality in the same species in the summer of 1970 (Comps, 1972). It can be considered, in 1973, that the successive losses lead to the quasi-extinction of the species C. angulata in the farms of the Marennes basin, since, contrary to what has been done in the case of the Malpèque disease in Canada, the indigenous specious was replaced by another species, the Pacific oyster Crassostrea gigas Thunberg. Un an apràs la fin de la maladie des branchies qui frappa gravement les huîtres portugaises Cassostrea angulata Lmk. (Marteil, 1968), une affection dont les causes sont restées encore indéterminées entraîna dès l'été 1970 une mortalité massive des huîtres de cette m@me espèce (Comps, 1972). On peut en 1973 considérer que les pertes successives ont conduit à la quasi disparition dans les parcs d'élevage du bassin de Marennes de l'espèce C. angulata puisque contrairement à ce qui a été fait dans le cas de la "maladie de Malpèque" au Canada, l'espèce indigène a été remplacé par une autre espèce, l'huître du Pacifique Crassostrea gigas Thunberg.